Nano-scale morphology of cardiomyocyte t-tubule/sarcoplasmic reticulum junctions revealed by ultra-rapid high-pressure freezing and electron tomography. (April 2021) - Rog-Zielinska, E.A.; Moss, R.; Kaltenbacher, W.; Greiner, J.; Verkade, P.; Seemann, G.; Kohl, P.; Cannell, M.B.
Abstract: Detailed knowledge of the ultrastructure of intracellular compartments is a prerequisite for our understanding of how cells function. In cardiac muscle cells, close apposition of transverse (t)-tubule (TT) and sarcoplasmic reticulum (SR) membranes supports stable high-gain excitation-contraction coupling. Here, the fine structure of this key intracellular element is examined in rabbit and mouse ventricular cardiomyocytes, using ultra-rapid high-pressure freezing (HPF, omitting aldehyde fixation) and electron microscopy. 3D electron tomograms were used to quantify the dimensions of TT, terminal cisternae of the SR, and the space between SR and TT membranes (dyadic cleft). In comparison to conventional aldehyde-based chemical sample fixation, HPF-preserved samples of both species show considerably more voluminous SR terminal cisternae, both in absolute dimensions and in terms of junctional SR to TT volume ratio. In rabbit cardiomyocytes, the average dyadic cleft surface area of HPF and chemically fixed myocytes did not differ, but cleft volume was significantly smaller in HPF samples than in conventionally fixed tissue; in murine cardiomyocytes, the dyadic cleft surface area was higher in HPF samples with no difference in cleft volume. In both species, the apposition of the TT and SR membranes in the dyad was more likely to be closer than 10 nm in HPF samples compared to CFD, presumably resulting from avoidance of sample shrinkage associated with conventional fixation techniques. Overall, we provide a note of caution regarding quantitative interpretation of chemically-fixed ultrastructures, and offer novel insight into cardiac TT and SR ultrastructure with relevance for our understanding of cardiac physiology. Graphical abstract: Unlabelled Image Highlights: The cardiac dyadic cleft,  where T-tubules and sarcoplasmic reticulum are closely opposed,  is key to cardiac excitation-contraction coupling. Most knowledge about the ultrastructure of the dyad comes from electron microscopic studies, traditionally involving chemical fixation. By using ultra-fast vitrification, we demonstrate that the dyadic cleft has dramatic qualitative and quantitative differences in morphology.